KH MUHAMMAD MUHAJIRIN AMSAR SEBAGAI PIONIR PENDIDIKAN ISLAM DAN REFORMASI SOSIAL UNTUK MENCERDASKAN KESADARAN UMAT DI KOTA BEKASI - Miftahul Huda; Ahmad Zamakhsari; Nabil (Almarhalah: Jurnal Pendidikan Islam, 2025)
This research is driven by the need to understand the role of Islamic education as a tool for social transformation within the complex context of urban society, particularly in Bekasi City. KH Muhammad Muhajirin Amsar is recognized as a figure who integrates Islamic education and social reform to cultivate a more critical and inclusive community awareness. The study aims to reveal the methods and strategies employed by KH Muhammad Muhajirin Amsar in developing progressive Islamic education that acts as an agent of social change. This study employs a literature review and qualitative analysis of documents, literature, and secondary sources related to Islamic educational leadership and social reform. Results indicate that KH Muhammad Muhajirin Amsar succeeded in creating an adaptive pesantren-based Islamic education model that meets modern demands and strengthens social awareness and solidarity through a dialogical and inclusive approach. The study confirms that integrating Islamic education with social reform serves as an effective instrument in fostering community social awareness, especially in urban settings such as Bekasi.This research contributes significantly to understanding the role of local figures in merging religious values with contemporary social dynamics, and paves the way for further studies on the relationship between Islamic education and social reform.